The work culture of public civil servants in Pauh District, Padang City - Fitri, Annisa; Mulia, Rizki Afri; Saputra, Nika; Wilinsky, Monica (Jurnal Ilmiah Ekotrans & Erudisi, 2025)
This study aims to analyze the work culture of Civil Servants (Aparatur Sipil Negara/ASN) in the administration of government at Pauh District, Padang City, and to explain the urgency of work culture in improving the quality of public services. The research employed a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation involving 12 informants consisting of district leaders, ASN staff, and community members as service recipients. The findings indicate that the work culture of ASN in Pauh District still requires strengthening, particularly in the aspects of time discipline, service professionalism, communication, and accountability. Analysis using the New Public Service (Denhardt & Denhardt) framework reveals that indicators such as service accessibility, community satisfaction, timeliness, fulfillment of information needs, fairness in service delivery, problem-solving ability, and accountability have not yet been fully optimized. The transformation of work culture toward democratic and participatory public service can only be achieved through strengthening work ethics, developing competencies, and enhancing individual awareness among civil servants regarding their responsibility to serve the public.